Hubungan Peran Keluarga Dengan Kepatuhan Minum Obat Pada Pasien Lansia Yang Menderita TB Paru Di Rumah Sakit Umum Pusat Haji Adam Malik Medan Tahun 2021 - Dina Afriani; Lisdayanti Simanjuntak; Petra Diansari Zega; Labora Br Manulang; Roida Sartika Dewi Simanullang; Habib Nabawi; Siti Nur Fadila (Universitas Muhamadiyah Manado, 2021)
Pulmonary TB is a major problem in the prevention and eradication of TB in the world. This study aims to determine the relationship between the role of the family and compliance with taking medication for elderly people suffering from pulmonary TB at the Adam Malik Haji Central General Hospital, Medan in 2021. This type of research is descriptive correlation with a cross sectional research design. The number of samples was 43 from April to June 2021. The research was conducted at RSUP. Human Rights at the MDR TB Polyclinic. Bivariate analysis used the chi-square test to determine the relationship between the role of the family and the role of nurses on medication compliance, while the multivariate analysis used medication compliance for elderly people suffering from multiple logistic pulmonary TB. Based on hypothesis testing using chi-square with a confidence level of 95%, it was found that there was a significant relationship between family role and medication adherence (p=0.01). There is a significant relationship between. Based on multivariate analysis, the variable that was most related to medication adherence in MDR TB sufferers was informational family support (p=0.01). The conclusion of this research is that there is a relationship between the supportive role of nurses and compliance with taking medication in TB sufferers.